The Guitar as a Laboratory for Experimentation - San Juan, Camilo A. Mendez (Revista Vórtex, 2020)
In this article, I will discuss the role of the electric guitar in the conception, development and composition of three recent works: Recessional Motion, Flexidra IV, and Volpi/Formentera. In Recessional Motion, I will address compositional, technical and notational issues to explain the underlying creative process. In Flexidra IV, all the pre-compositional materials were the result of extensive experimentation sessions with electric guitars, pedals and found objects that subsequently were extrapolated to other instruments to generate the instrumental textures. In Volpi/Formentera, the electric guitar is at the centre of the compositional processes and all the musical parameters orbit around it. I will examine in detail how the different preparations and instrumental textures were derived from my own "˜exploratory sessions' presenting possible solutions to notate the necessary actions to produce the sounds in the guitar.